Interior Memory: a re-imagining of home. (2nd January 2016) - Salen, Pamela
Abstract: This paper examines how narratives of domestic space can be re-imagined after the space has been vacated. It is based on a recent practice-led study that engaged with twenty participants to describe a past room and their memories located within. Visual narrative analysis and the photogram are the methodologies used whereby the participant's text is interpreted by the researcher in visual translation for the participant to respond to. This research explores how memories are affected when prompted by a re-created image suggestive of an individuals' once-inhabited room. The interior is translated as photogram images in an effort to challenge photographic realism and to invite a dialog between imagination and memory located within the home as the context for a larger narrative about representation and meaning. The photogram is a photographic image made without the use of a camera pre-dating the invention of camera photography. It is based on chemically treated light-sensitive paper and a light source. The photogram images made in this study are sunlight exposed, as opposed to controlled darkroom exposure, resulting in warm-toned and unpredictable images. The images are disassociated from accurate translations of place and instead explore the relations between the emotive language of light and shadow and the spatial and sensual qualities that begin to define experiences attached to home and memories. This study opens up new ways by which domestic space is imagined, produced, and discussed to facilitate a co-creation of meaning between individuals, practitioners, and researchers in art, design, architecture, and social sciences.